2009
DOI: 10.1016/j.precamres.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

SHRIMP zircon U–Pb age constraints on Neoproterozoic Quruqtagh diamictites in NW China

Abstract: The Neoproterozoic Quruqtagh Group in the Tarim Block, NW China, contains multiple diamictites in the Bayisi, Altungol, Tereeken, and Hankalchough formations. These diamictites may represent three or possibly four discrete glaciations, although evidence for a glacial origin of the Bayisi and Altungol diamictite is ambiguous. To constrain their age and duration, we dated three volcanic beds (V1, V2, and V3) in the Quruqtagh Group using the SHRIMP (sensitive high-resolution ion microprobe) zircon U-Pb method. Vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
130
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(140 citation statements)
references
References 59 publications
5
130
0
5
Order By: Relevance
“…The Altungol Formation unconformably overlies the Bayisi Formation and is conformably overlain by Tereeken Formation. The Zhaobishan Formation, which is reported in the other sections (such as Xishankou section and Yukengou section) (Shen et al 2008;Xu et al 2009), is missing in the Yaerdany area. In the YI section, the Altungol Formation consists of a ∼45-m-thick tillite, a ∼5-m cap dolostone, and a ∼20-m shale.…”
Section: Regional Geologymentioning
confidence: 91%
See 3 more Smart Citations
“…The Altungol Formation unconformably overlies the Bayisi Formation and is conformably overlain by Tereeken Formation. The Zhaobishan Formation, which is reported in the other sections (such as Xishankou section and Yukengou section) (Shen et al 2008;Xu et al 2009), is missing in the Yaerdany area. In the YI section, the Altungol Formation consists of a ∼45-m-thick tillite, a ∼5-m cap dolostone, and a ∼20-m shale.…”
Section: Regional Geologymentioning
confidence: 91%
“…A volcanic unit in the topmost Bayisi Formation gave a SHRIMP zircon U-Pb age of 725 ± 10 Ma (Xu et al 2009). He et al (2014) reported U-Pb zircon ages of 655.9 ± 4.4 and 654 ± 10 Ma from the upper Altungol Formation in Quruqtagh.…”
Section: Regional Geologymentioning
confidence: 99%
See 2 more Smart Citations
“…Middle Neoproterozoic to Phanerozoic rocks consist of mafic dyke swarms, bimodal volcanics as well as fine sandstones, siltstones, shales, dark limestones and chert nodule-bearing dolomites. The mafic dykes with bimodal volcanics were formed at 820-744 Ma and 650-630 Ma (Zhang et al 2007a;Zhu et al 2008;Xu et al 2009). Late Neoproterozoic glacial deposits are also well exposed (Xu et al 2009).…”
Section: Geological Settingmentioning
confidence: 99%